Study of The Ecological Populations and Nesting Oecophylla smaragdina FABR. on Oil Palm Plantations as A Biological Control Indicator - Falahudin, Irham; Alfarabi, Thoriq (Al-Kauniyah: Jurnal Biologi, 2025)
Weaver ants (Oecophylla smaragdina Fabr.) are social insects that have an ecological role in ecosystems of oil palm plantations. Oecophylla is a predator that prevents ant prey and influences interspecies competition. The study of the ecological population of Oecophylla smaragdina Fabr. Has not been reported, focusing on measuring nest and population density in plantations with varying ages. Important research in understanding the role of Oecophylla as a potential biological control agent in plantations. The purpose of the study was to determine the population density and nest as indicators of biological control. The study was conducted in Banyuasin Regency, South Sumatra, with a purposive sampling method, collecting ant nest data based on variations in plant age. The results of our study found that the number of individuals was 4,782 from various nests. The nests found were round and oval with an area ranging from 4.19–24.19 cm². The nests found were at a height of between 1 m and 3.4 m. Population and the formation of nests are also influenced by abiotic and biotic factors. The formation of nests is an indication of interactions between species and is an important factor in the study of the population ecology of Oecophylla as a biological control.